Pink Eye Cases in Goats at The Sawangan Farm - Henny Endah Anggraeni; Yvette Rafi (Universitas Airlangga, 2021)
Background: Pink eye disease in goats causes blindness, weight loss, and expensive medical costs, resulting in losses on farmers. Purpose: The purpose of this case study is to provide information regarding the handling of Pink Eye cases in goats in Sawangan Farms. Method: Observation data presented descriptively were compared and discussed with supporting data from literature. Treatment of Pink Eye cases in 36 goats at Sawangan Farm was started by separating the affected goats, then topical therapy was provided with Super Tetracycline HCl 250 mg® in 1% warm orange water. Topical treatment was carried out once a day by spraying 5-10 ml of the solution on both eyes of the goat for a month. Results: Healing of the goat's eye occurs within 2 weeks. Conclusion: The goat's eyes improved and looked clear again after treatment.